(untitled) (Bangladesh Journal of Botany, 2015)
Field experiments were conducted for three years during Kharif 2009-2011 to study the effect of foliar application of nutrients (N, Mg, Fe, Zn, Mn and B) on growth and yield parameters of Bt cotton. Pooled data indicated highest seed cotton yield (3421.4 kg/ha) with application of MgSO4 1.0%+ ZnSO4 0.5%. Better net returns ( 100760/ha) and improved B:C (4.06) ratio for MgSO4 1.0% + ZnSO4 0.5% clearly supported its application benefits to realize higher yield . DOI: http://dx.doi.org/10.3329/bjb.v44i1.22717 Bangladesh J. Bot. 44(1): 9-14, 2015 (March)